2008
DOI: 10.1097/01.cnq.0000325051.91473.42
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Continuous Lateral Rotation Therapy in Overall Clinical and Financial Outcomes of Critically Ill Patients

Abstract: Continuous lateral rotation therapy, when introduced early in course of treatment of high-risk patients, reduces critical care LOS and cost to treat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 21 publications
0
34
0
2
Order By: Relevance
“…McKay 6 suggested that CLRTs achieve the best outcomes when implemented within 24 to 48 hours of meeting set criteria and are maintained for at least 18 hours per day. SwadenerCulpepper et al 8 reported that CLRT patients in an early intervention group (implemented within 48 hours of meeting criteria) fared much better on the outcome criteria evaluated than did the late intervention group (CLRT implemented more than 48 hours after criteria were met). Therefore, early identification of patients who could benefit from therapy has the best potential for improving outcomes.…”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…McKay 6 suggested that CLRTs achieve the best outcomes when implemented within 24 to 48 hours of meeting set criteria and are maintained for at least 18 hours per day. SwadenerCulpepper et al 8 reported that CLRT patients in an early intervention group (implemented within 48 hours of meeting criteria) fared much better on the outcome criteria evaluated than did the late intervention group (CLRT implemented more than 48 hours after criteria were met). Therefore, early identification of patients who could benefit from therapy has the best potential for improving outcomes.…”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%
“…If rotation is stopped at all, it should be stopped only for long enough to deal with the underlying cause of the instability. 8 Evaluation of the patient's oxygen levels, respiratory rate, ventilator settings, arterial blood gas levels, and other parameters may reveal the need for interventions in other areas that would minimize desaturation during rotation. Decreasing the time and depth of rotation to the side where the greatest desaturation occurs can improve tolerance as well.…”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…It is appropriate to use pillows and other positioning devices during the 6 hours of non-CLRT therapy. [5][6][7][8][9][10][11] …”
Section: Continuous Lateral Rotation Therapymentioning
confidence: 99%